a Analisis Potensi Gastronomi Nasi Cengklik Sebagai Upaya Peningkatan Wisata Kuliner Di Waduk Cengklik, Boyolali - Purnaningsih, Sri; Hendry Gigih Saputra; Roni Kurniawan; Dethi Susanti; Muhammad Rizky Nur Hidayat (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2025)
This study aims to analyze Nasi Cengklik food as a gastronomic potential in Cengklik Reservoir, Boyolali, Central Java. Culinary rice cengklik is a traditional food that has never been studied, so it has its own charm to be researched. The method applied in this research is a product development research method with 4 D steps: define, design, develop and disseminate as well as a descriptive method based on a theoretical basis. The data collection method used primary data in the form of observations, interviews with tourism managers and traditional food makers, and secondary data in the form of journals, documents related to tourism, culinary. Data analysis in this study is a descriptive analysis of the data collected and then draw conclusions. The results showed that cengklik rice is a traditional culinary that can support the existence of cengklik reservoir. This can be seen from the uniqueness, originality, authenticity and diversity that can be seen from the traditional way of cooking, the distinctive taste resulting from the use of local ingredients and products, such as the use of brown rice, genjer leaf midrib, and side dishes from wader pari served with pincuk leaves banana that add a classic feel and value to the dish. Keywords: : Gastronomy, Nasi Cengklik, Culinary Tourism.